A Comparison of the Targeted and Analytic Performance of a Post-Tensioned Frame Structure Through Fragility Analysis - Kircil, Murat Serdar; Kirici, Zeynep (MDPI, 2024)
Buildings designed in accordance with Earthquake Codes are expected to survive slight earthquakes without damage, moderate earthquakes with limited and repairable damage, and severe earthquakes without collapse and loss of life. These definitions can be considered as target performance levels; however, whether the performance targets have been achieved is not verified using an engineering parameter. It is assumed that a structure designed in accordance with the code regulations will meet the prescribed controlled damage behavior and that the risk to life safety is minimum. However, studies examining the accuracy of this assumption in terms of the probability of exceeding the targeted performance levels are not widely available in the literature. The purpose of this study is to investigate to what extent this assumption is realistic. The targeted and analytically determined performance of the examined post-tensioned reinforced concrete frame building was compared through the generated fragility curves. The results show that the analytical performance of the examined building does not completely comply with the targeted performance defined by the Turkish Seismic Design Code; therefore, the assumption that a structure designed in accordance with the code will exhibit the targeted performance is not always realistic for each type of building.
Keywords: fragility curves; post-tensioned frame; damage estimation; performance; incremental dynamic analysis; SEISMIC PERFORMANCE; BUILDINGS; VULNERABILITY; METHODOLOGY; Construction & Building Technology; Engineering